Speech in implant-supported and removable complete denture wearers: A systematic review - Meira, Ingrid Andrade; Gama, Lorena Tavares; Prado-Tozzi, Daniela Almeida; Pinheiro, Mayara Abreu; Rodrigues Garcia, Renata Cunha Matheus (The Journal of prosthetic dentistry, 2022)
Prosthetic rehabilitation, especially with removable complete dentures (CDs), can contribute to speech problems, although the prevalence of the problem is unclear. The purpose of this systematic review was to examine the influence of implant-supported fixed complete dentures (FCDs), implant-supported overdentures, and removable CDs on speech articulation disorders in patients with at least 1 completely edentulous jaw. This study was prepared according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered in the International Prospective Register of Systematic Reviews (CRD42020182705). The PubMed/Medline, Embase, Web of Science, Scopus, Latin American and Caribbean Health Sciences, Brazilian Clinical Trials Registry, and Cochrane Library databases were searched through April 2020 to identify clinical trials comparing maxillary and/or mandibular implant-supported dentures with removable CD use in terms of speech articulation in participants with at least 1 completely edentulous jaw. The risk of bias of selected studies was assessed with the Joanna Briggs Institute critical appraisal tools, and the quality of evidence was tested by using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Initially, 2586 articles were identified, and their titles and abstracts were read. Sixteen articles were read in full, and 8 studies (4 paired clinical trials and 4 cross-sectional studies) were included in this review. In total, 290 prosthesis users aged 29 to 90 years, approximately 44 of whom had hearing difficulties, were included. Four studies had a low risk of bias, and 4 studies had a high risk of bias. Distortions of the /s/ phoneme were observed more often in the first 6 months of maxillary FCD use than with removable CD use. Speech articulation did not differ between mandibular FCD and removable CD users. The quality of evidence for speech articulation disorders was low. Given the low quality of evidence on speech articulation disorders, further research on speech articulation disorders in prosthesis wearers is needed.